Genetic Engineering in Refinning Of Wastewater - Öbek, Erdal; Atalan, Ekrem; İpek, Übeyde; Hasar, Halil (Van Yüzüncü Yıl Üniversitesi, 1999)
Microorganisms are known that have active role in recycling of different kind waste into harmless form. To refıne wastewater a new stable mutant microorganisms can be developed using genetic engineering techniques. Genetic engineering involve the genetic manipulation of microorganisms for refıning of wastewater. Since refining process consist of various field, genetic engineering, microbiology, physiology, ecology, biochemistry, molecular biology and process engineering should make col[aborative stüdy. Any scientifıc discipline do not contain sufficient information to solve the problem of refining of waste and wastewater. Thus, it is difficult to define appropriate microorganisms and physical factors in environmental app[ications.

Mikroorganizmalar farklı tipteki atık maddeleri zararsız hale dönüştürmede aktif rolleri olduğu bilinmektedir. Atık suların artırılmasında genetik mühendisliği teknikleri kullanılarak yeni ve değişmeyen mutant mikroorganizmalar geliştirebilir. Atık suların artımında kullanılan mikroorganizmalar günümüzde rekombinant DNA tekniği kolayca değiştirilmektedir. Genetik Mühendisliği, mikrobiyoloji, fizyoloji, ekoloji, biyokimya ve moleküler biyoloji bilim dalları arıtma işlemleri ile alakalı olduğundan arıtma sorunun çözümünde tüm bilim dallarının arasında işbirliği olması gerekir. Tek bir bilim dalı atık madde ve atık su arıtımı ile ilgili problemleri çözmek için yeterli bilgi içermez Ayrıca çevresel uygulamarda hem uygun mikroorganizma hemde fiziksel faktörlerin tanımlanması önemlidir.
Atıksu Arıtımında Genetik Mühendisliği